2020
DOI: 10.1051/0004-6361/201936726
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia-ESO Survey: Spectroscopic-asteroseismic analysis of K2 stars in Gaia-ESO

Abstract: Context. The extensive stellar spectroscopic datasets that are available for studies in Galactic Archeaology thanks to, for example, the Gaia-ESO Survey, now benefit from having a significant number of targets that overlap with asteroseismology projects such as Kepler, K2, and CoRoT. Combining the measurements from spectroscopy and asteroseismology allows us to attain greater accuracy with regard to the stellar parameters needed to characterise the stellar populations of the Milky Way. Aims. The aim of this Ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 107 publications
2
7
0
Order By: Relevance
“…We derive the stellar parameters for the 52 GES-K2 stars using LOTUS. Our results for log g and T eff as compared to Worley et al (2020) are shown in Figure 9 agree well with the photometric and asteroseismic parameters from Worley et al (2020) within their error bars, however our NLTE parameter derivations agree better for both T eff and, particularly for log g.…”
Section: Ges-k2 Starssupporting
confidence: 78%
See 2 more Smart Citations
“…We derive the stellar parameters for the 52 GES-K2 stars using LOTUS. Our results for log g and T eff as compared to Worley et al (2020) are shown in Figure 9 agree well with the photometric and asteroseismic parameters from Worley et al (2020) within their error bars, however our NLTE parameter derivations agree better for both T eff and, particularly for log g.…”
Section: Ges-k2 Starssupporting
confidence: 78%
“…The average uncertainties reported in Worley et al (2020) for T eff and log g of the GES-K2 stars are ±65 K and ±0.02, respectively. We note that these values are close to our parameter grid resolution.…”
Section: Ges-k2 Starsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Gaia-ESO Public Spectroscopic Survey is designed to obtain high quality and high resolution spectra of some 100 000 Milky Way stars (Gilmore et al 2012;Smiljanic et al 2014;Worley et al 2020). Gaia-ESO observed stars using the medium-resolution spectrograph GIRAFFE (R ∼ 20 000) and the high-resolution spectrograph UVES (R ∼47 000) mounted on the VLT.…”
Section: Comparing Our Effective Temperature With That Provided By Ga...mentioning
confidence: 99%
“…Apart from the GBS, several samples of calibrating stars, with accurate masses, have become available thanks to recent advances in asteroseismology (Valentini et al 2016(Valentini et al , 2017Serenelli et al 2017;Pinsonneault et al 2018;Worley et al 2020). Stars in eclipsing binaries are an additional option for use as calibrators.…”
Section: Introductionmentioning
confidence: 99%